Implementasi Metode Brain-Based Learning dalam Pendidikan Agama Islam - Nurwastuti Setyowati (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2022)
The aims of this research was to analyze the learning outcomes of Islamic Education (PAI) subjects at SMK N 1 Saptosari by applying the Brain-Based Learning method. The type of research used was experimental research using quantitative research methods. The data collection technique chosen was the non-equivalent control group design test and a questionnaire that analyzed the comparison of learning outcomes and learning motivation for the experimental class and the control class. The data sources of this research were the pre-test and post-test scores as well as a learning motivation questionnaire from the respondents. The findings of this research were that there were significant differences in the learning outcomes and learning motivation of students in the control class and the experimental class due to differences in the learning methods applied. The final conclusion from this research was that the use of Brain-Based Learning methods for Islamic education in PAI material had a higher percentage in the experimental class than in the control class. It showed that the Brain-Based Learning method could improve student learning outcomes when applied to material that was relevant and relevant to students.